On Monotonic Solutions of A Nonlinear Integral Equation of Volterra Type - Osman Karakurt; Ö. Faruk Temizer (Journal of Advances in Applied & Computational Mathematics, 2016)
We study a nonlinear integral equation of Volterra type in the Banach space of real functions defined and continuous on a bounded and closed interval. Using a technique associated with measure of noncompactness we prove the existence of the nondecreasing solutions to a nonlinear integral equations of Volterra type in C [0, 1]. We give also one example satisfying the conditions of our main result but not satisfying the conditions of the main result in [1].